2016
DOI: 10.1016/j.bbmt.2015.09.027
|View full text |Cite
|
Sign up to set email alerts
|

Donor Immunization Against Human Leukocyte Class II Antigens is a Risk Factor for Graft-versus-Host Disease

Abstract: The sensitization to HLA antigens is caused mainly by pregnancy and transfusions; however, anti-HLA antibodies also may be detected in nulliparous females and nontransfused males, and thus specifically in hematopoietic stem cell transplantation (HSCT) donors. In such cases, the impact on HSCT outcome is known only for platelet transfusion refractoriness. This study addresses the impact on graft-versus-host disease (GVHD) of anti-HLA antibodies detected in voluntary unrelated donors. Among 100 donor/recipient (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 50 publications
1
15
1
Order By: Relevance
“…At present, there is no formal testing of donors for the presence of antibodies reactive with HLA mismatches of the recipient; recipient‐specific antibodies (RSA). One single‐centre study has described an increased incidence of either aGVHD or cGVHD in patients transplanted with donors who were sensitized to HLA class II, predominantly mismatched HLA‐DPB1 alleles (Delbos et al., 2016). It has been reported that donor‐derived HLA antibodies can be detected post‐transplant in patients transplanted with donors that are positive for HLA antibodies which suggests they could impact on engraftment in HLA‐mismatched transplants (Taniguchi et al., 2012).…”
Section: Hla Alloantibodiesmentioning
confidence: 99%
“…At present, there is no formal testing of donors for the presence of antibodies reactive with HLA mismatches of the recipient; recipient‐specific antibodies (RSA). One single‐centre study has described an increased incidence of either aGVHD or cGVHD in patients transplanted with donors who were sensitized to HLA class II, predominantly mismatched HLA‐DPB1 alleles (Delbos et al., 2016). It has been reported that donor‐derived HLA antibodies can be detected post‐transplant in patients transplanted with donors that are positive for HLA antibodies which suggests they could impact on engraftment in HLA‐mismatched transplants (Taniguchi et al., 2012).…”
Section: Hla Alloantibodiesmentioning
confidence: 99%
“…Indeed, in unrelated donor-recipient settings, the presence of anti-HLA-DPB1 antibodies was clinically relevant with respect to development of transplant-related complications, including cGvHD. The outcome of having HLA antibodies in voluntary unrelated donors was analyzed by Delbos et al ( 47 ). They observed a significantly higher cumulative incidence of cGvHD in recipients transplanted with anti-HLA class II immunized donors, directed mainly against HLA-DPB1 alleles.…”
Section: Alloantibodies and Gvhdmentioning
confidence: 99%
“…Theoretically, recipient-specific anti-HLA antibodies also might affect the development of GvHD [ 22 ]. In a recent study, Delbos et al evaluated 82 HLA class II mismatched unrelated transplant donor–recipient pairs [ 76 ]. In this cohort, 26 donors (32%) had at least one anti-HLA class II antibody in peripheral blood.…”
Section: Donor Specific Anti-hla Antibodies: Dream or Reality?mentioning
confidence: 99%